The role of natalizumab in the treatment of multiple sclerosis: benefits and risks. (September 2017) - Singer, Barry A.
Natalizumab, a monoclonal antibody that blocks lymphocyte infiltration in the central nervous system, is a valuable tool in the treatment of relapsing forms of multiple sclerosis (MS). In a phase III clinical trial comparing natalizumab with placebo over 2 years, natalizumab reduced annualized relapse rate by 68%, 12-week confirmed disability progression by 42%, and reduced contrast-enhancing lesions by 92%. In post hoc analyses, natalizumab treatment was associated with 37% of patients achieving no evidence of disease activity ( versus 7% on placebo) and 30% achieving sustained disability improvement ( versus 19% on placebo). Natalizumab did not achieve a statistically significant primary composite disability outcome in a trial of 887 patients with secondary progressive MS, but it did demonstrate a benefit on a prespecified component of the 9-Hole Peg Test. The greatest risk of natalizumab treatment is progressive multifocal leukoencephalopathy (PML), with a 23% mortality rate. Risk stratification on the basis of immunosuppressant exposure, natalizumab treatment duration and anti-John Cunningham virus (JCV) antibody status and index has greatly improved clinical decision making. Other potential serious natalizumab-associated risks reported in clinical trials and postmarketing settings include infusion reactions, hepatotoxicity and rare, serious opportunistic infections. With more than a decade of continuous postmarketing experience, natalizumab remains a very effective option for patients with relapsing forms of MS. To optimize appropriate selection of natalizumab for patients with relapsing MS, however, a thorough understanding of individual patient risk factors for PML or other adverse events is also required.